Uma proposta para aplicação de mapas conceituais ao processo de ensino-aprendizagem de computação - Brezolin, Ligia Maria Teixeira de Faria (2010)
This research is a proposal for the application of concept maps in Higher Education Computing in two aspects: the integration of disciplines that make up the curriculum, as well as in students learning, leading them to a meaningful learning. Higher education is seen as a challenge in creating techniques that can be a potential factor in student learning in a way they could study and learn the subjects contents in a more enjoyable way. The study was based on the qualitative analysis, having as a theoretical reference Ausubel, Novak, Gowin, Gagné, Piaget and Bruner. The concepts related to teaching and learning are discussed, highlighting the cognitive theory of learning and concept maps. The research was carried out in Computing Science Course at UNISAL - Centro Universitário Salesiano de São Paulo Unidade de Ensino de Lorena, in the subject Object-Oriented Programming Language. The teacher and the students of first year (second semester) course were the subjects of the research. The activities related to the course contents and the use of concept maps across the CmapTools software and analysis of the maps developed by the students were carried out during the research. The results showed that the implementation of the concept maps technique in the teaching of computing was a potential learning facilitator action as well as to allow this occurrence in other disciplines of the course